Electron Microscopic Evidence of Photoreceptor Outer-segments in the Trabecular Meshwork in a Case of Schwartz-Matsuo Syndrome. Issue 9 (September 2019) - Clark, Antony; Alkhotani, Alaa; Yucel, Yeni H.; Sylvester, Carly; Kertes, Peter J.; Birt, Catherine M.
Abstract : Purpose: To describe a case of photoreceptor outer segment glaucoma (Schwartz-Matsuo syndrome) with electron microscopic evidence of photoreceptor outer segments in the trabecular meshwork (TM). Design: This is a clinicopathologic case report. Participant: A 48-year-old Filipino man. Methods: Specimens of aqueous humor and TM in a clinical case of Schwartz-Matsuo syndrome were examined by electron microscopy. Main Outcome Measures: Electron photomicroscopy. Results: Electron microscopy showed evidence of retinal photoreceptor outer-segments in both an aqueous humor and a TM specimen. Conclusion: Schwartz-Matsuo syndrome is associated with the presence of photoreceptor outer segments in the TM.